The Monseigneur and the grands seigneurs: questions of priority in early modern France - Sternberg, G (Oxford University Press, 2019)
This article investigates a series of epistolary contestations among the French high command in the seventeenth and eighteenth centuries in order to unlock their far-reaching military, political, cultural and social ramifications. Remarkably, disagreements over the use of the term Monseigneur and other epistolary status-markers took priority over military expediency, disrupting French armed operations in the midst of external war or internal rebellion. Such priority of traditional values over new ideals of royal service qualifies the thesis of a reconfiguration of noble Mentalités under the Bourbon monarchy. What is more, close analysis of these conflicts and tensions reveals their impact on everyday communication, sociability and friendship, and uncovers a rich spectrum of coping strategies, from open confrontation to subtler forms of evasion or accommodation. Drawing on new archival findings as well as on a reinterpretation of celebrated literary texts, this analysis also serves to recontextualise these writings as part of information networks that played an active role in the conflicts themselves. Finally, the underlying contestations over social priority newly illuminate the changing landscape of the French aristocracy during this period, revealing points of fissure, collective identities and moments of transformation. In particular, the article brings into relief the changing fortunes of those who remained part of the aristocratic system but did not obtain the positions that increasingly became emblematic of the highest rank. These contestations thus powerfully illustrate how epistolary ceremonial, and cultural practices more generally, can advance our understanding of social structures and dynamics.